(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses the moral principles of patriotism, which are relevant at all times and are relevant today. Patriotism is one of the most ancient feelings of people, which at all times had a concrete historical content and its own specifics. The consequence of this was the national and universal aspects of patriotism. Patriotism is an ethnogenetic, natural-legal, moral, economic and political, religious feelings associated with all spheres of society’s life that arise in the psyche of people on a certain geographical territory, within a certain community or nation. It is included in the attributive properties of a number of forms of social consciousness and acts as a coordination of certain beliefs and behavior. Patriotism is a spiritual phenomenon with its substantial integrity. It is from this point of view that the article highlights the socio-philosophical features of patriotism.